Local diversity of fruit, nut trees and grapevine as basis of organic horticulture development in Uzbekistan - Turdieva, M.K.; Baymetov, K.I.; Kayimov, A. (Tashkent State Agrarian University, 2016)
This paper (in Russian) discusses the possibility of development of organic fruit growing in Uzbekistan using rich varietal diversity of local fruit crops.